A Universal Positive-Negative Selection System for Gene Targeting in Plants Combining an Antibiotic Resistance Gene and Its Antisense RNA. Issue 1 (4th July 2015) - Nishizawa-Yokoi, Ayako; Nonaka, Satoko; Osakabe, Keishi; Saika, Hiroaki; Toki, Seiichi
Abstract : A positive-negative selection system based on a combination of an antibiotic resistance gene and its antisense RNA can enrich gene-targeted cells in rice. Abstract: Gene targeting (GT ) is a useful technology for accurate genome engineering in plants. A reproducible approach based on a positive-negative selection system using hygromycin resistance and the diphtheria toxin A subunit gene as positive and negative selection markers, respectively, is now available. However, to date, this selection system has been applied exclusively in rice ( Oryza sativa ). To establish a universally applicable positive-negative GT system in plants, we designed a selection system using a combination of neomycin phosphotransferaseII ( nptII ) and an antisense nptII construct. The concomitant transcription of both sense and antisense nptII suppresses significantly the level of expression of the sense nptII gene, and transgenic calli and plants become sensitive to the antibiotic geneticin. In addition, we were able to utilize the sense nptII gene as a positive selection marker and the antisense nptII construct as a negative selection marker for knockout of the endogenous rice genes Waxy and 33-kD globulin through GT, although negative selection with this system is relatively less efficient compared with diphtheria toxin A subunit . The approach developed here, with some additional improvements, could be applied as a universal selection system for the enrichment of GT cells in several plant species.